The odd quantum - Treiman, Sam B.; Quinn, Helen R. (Princeton : Princeton University Press, 2024)
A concise but comprehensive account of quantum mechanics for popular science readers written by a respected physicist. Sam Treiman--who was internationally renowned for his work in particle physics--makes quantum mechanics accessible to nonspecialists. Combining mastery of the material with clear, elegant prose and infectious enthusiasm, he conveys the substance, methods, and profound oddities of the field.Treiman begins with an overview of quantum mechanics. He sketches the early development of the field by Einstein, Bohr, Heisenberg, Schrödinger, and others, and he makes clear how the quantum outlook flies in the face of common sense. As he explains, the quantum world is intrinsically probabilistic. For example, a particle is not in general in some particular place at a given instant, nor does it have a definite momentum. According to the Heisenberg uncertainty principle, there is a limit to how well both location and momentum can be specified simultaneously. In addition, particles can move through barriers and otherwise move in regions of space that are forbidden by classical mechanics. If a particle has a choice of different paths, it pursues all of them at once. Particles display wave-like characteristics and waves show particle-like characteristics. Treiman pays special attention to the more fundamental wave outlook and its expression in quantum field theory. He deals here with the remarkable fact that all the particles of a given species are strictly identical, and with the unnerving fact that particles can be created and destroyed. As Treiman introduces us to these and other wonders, he also touches-without resolution-on some of the deep philosophical problems of quantum mechanics, notably how probabilities become facts.Weaving together impeccable science, engaging writing, and a talent for clear explanation honed over Treiman's distinguished career as a physicist and teacher, The Odd Quantum is a remarkable survey of a field that changed the course of modern scientific and philosophical thought.
Frontmatter -- CONTENTS -- Foreword to the Princeton Science Library Edition -- Preface -- 1. Introduction -- 2. Classical Background -- 3. The "Old" Quantum Mechanics -- 4. Foundations -- 5. Some Quantum Classics -- 6. Identical Particles -- 7. What's Going On? -- 8. The Building Blocks -- 9. Quantum Fields -- Readings -- Index
Originally published: 1999.
Includes bibliographical references (pages 255-256) and index.
Online resource; title from PDF (viewed April 9, 2024).
JSTOR
Keywords: Quantum theory; Physics; Physique; Théorie quantique; physics; SCIENCE / Physics / General